New Forms of Communication in Regional Development Planning Illustrated with an Example of Masterplanprozess “Mensch und Land” - Piszczek, Elwira (Eastern European Countryside, 2024)
Laschewski, L., Wendt, W., (eds.), 2015. Die Zukunft der Landwirtschaft als dialogisches Verfahren. Rostock, HIE-RO.